Data on bacterial abundance from adaptation experiment - Andersson, Martin (Uppsala University, 2018)
Bacterial abundance data from adaptation experiment. Includes the growth of 16 samples that were regrown weekly over a time period of 6 weeks.

The dataset was originally published in DiVA and moved to SND in 2024.

Data om bakterieöverflöd från anpassningsexperiment. Omfattar tillväxten av 16 prover som återväxte varje vecka under en tidsperiod på 6 veckor.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on bacterial abundance from adaptation experiment
Abundance data adaptation experiment
Keywords: lakes; sjöar; bacteria; bakterier; Microbiology; Mikrobiologi